How do you implicitly differentiate # x^2+x/y-xy^2+x=3y #?

Answer 1

#(dy)/(dx)=(2xy^2+y-y^4+y^2 )/(3y^2+x+2xy^3) = f^'(x)#

#color(blue)("The teaching bit")# By example: Suppose we had #y^2+3y=x^4#
Let #z=y^2+3y-> (dz)/(dy)= 2y+3#...................(1) Then #z=x^4->(dz)/(dx)=4x^3#...............................(2)
'.................................................................................................................. Consider equation (1). If we can convert #(dz)/(dy)# to #(dz)/(dx)# then we can directly equate the Eqn(1) to Eqn(2)
We use:#" "(dz)/(cancel(dy))xx(cancel(dy))/(dx)#

But from Eqn(1)

#(dz)/(dy)=2y+3" "# so #" "(dz)/(dy)xx(dy)/(dx)" "=" "(dy)/(dx)(2y+3)#
so we have #(dy)/(dx)(2y+2)=(dz)/(dx)=4x^3#
Thus #(dy)/(dx)=(4x^3)/(2y+2)#
.================================================= #color(blue)("Answering the question")# Differentiating each term independently
As appropriate use #(d)/(dx)(uv)=v(du)/(dx)+u(dv)/(dx)#
As appropriate use #(d)/(dx)(u/v)=(v(du)/(dx)-u(dv)/(dx))/v^2# '................................................................................ #d/(dx)(x^2)=color(brown)(+2x)#
#d/(dx)(x/y)=color(brown)( ( y-x(dy)/(dx))/y^2)#
#d/(dx)(-xy^2) = -[y^2+x2y(dy)/(dx)]=color(brown)(-y^2-2xy(dy)/(dx)#
#d/(dx)(x)=color(brown)(+1)#
#d/(dx)(3y) =color(brown)( 3(dy)/(dx))# '........................................................................................ #color(brown)("Putting it all together")#

The differentiated equation is:

#2x+(y-x(dy)/(dx))/y^2 -y^2-2xy(dy)/(dx) +1=3(dy)/(dx)#

Collecting like terms

#3(dy)/(dx) + (x(dy)/(dx))/y^2+2xy(dy)/(dx)=2x+cancel(y)/y^(cancel(2))-y^2+1 #
#(3y^2(dy)/(dx)+x(dy)/(dx)+2xy^3(dy)/(dx))/y^2=2x+1/y-y^2+1#
#(dy)/(dx)(3y^2+x+2xy^3)=y^2(2x+1/y-y^2+1)#
#(dy)/(dx)=(2xy^2+y-y^4+y^2 )/(3y^2+x+2xy^3)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To implicitly differentiate the given equation ( x^2 + \frac{x}{y} - xy^2 + x = 3y ), follow these steps:

  1. Differentiate each term of the equation with respect to ( x ).
  2. Apply the product rule and chain rule where necessary.
  3. Solve for the derivative.

The implicit differentiation of the given equation yields:

[ 2x + \left( \frac{1}{y} - y^2 \right) - y^2 - x + 1 = 3 \frac{dy}{dx} ]

Simplify the equation to isolate ( \frac{dy}{dx} ):

[ \frac{dy}{dx} = \frac{2x + \frac{1}{y} - 2y^2 - x + 1}{3} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7